Uji Fitokimia dan Aktivitas Antioksidan Ekstrak Metanol Daun Kelor (Moringa oleifera) Melalui Ekstraksi Maserasi - Siskawati; Haeruddin; Nurlansi (Jurusan Pendidikan Kimia FKIP Universitas Halu Oleo, Jl. HEA. Mokodompit Kampus Hijau Bumi Tridharma Andounohu Kendari, Gedung MIPA FKIP UHO Sulawesi Tenggara – Indonesia, 2023)
Phytochemical Tests and Antioxidant Activity of Moringa Leaf (Moringa oleifera) Methanol Extract Through Maceration Extraction Research has been carried out. This study aims to determine the secondary metabolites and antioxidant activity of Moringa Leaf Methanol Extract (Moringa oleifera). Secondary metabolite compounds contained in the ethanol extract of Moringa leaves were determined by the phytochemical method, while the antioxidant activity was determined by the DPPH method. Moringa leaves used are dried Moringa leaves that have been mashed. A total of 750 g of soni leaves were macerated for 3x24 hours with methanol as solvent. The extracts were then collected and concentrated to obtain a thick extract of 139.5668 g. The extracts were tested for phytochemicals and antioxidants. Phytochemical test results showed that the methanol extract of Moringa leaves contains alkaloids, flavonoids, steroids, saponins and polyphenols. The methanolic extract of Moringa leaves has a weak antioxidant activity with an IC50 value of 290.10 ppm.